Outcome of neoadjuvant chemotherapy followed by concurrent chemoradiotherapy versus concurrent chemoradiotherapy alone in non-metastatic locally advanced non-small cell lung cancer – A prospective and randomized study - Subir Pal; Anjan Bera; Soumen Mukherjee; Asmita Dasgupta; Srikrishna Mandal; Saptarshi Banerjee (Asian Journal of Medical Sciences, 2023)
Background: Sequential chemoradiotherapy and concurrent chemoradiotherapy are two treatment options for locally advanced non-small cell lung cancer (NSCLC). Still there is limited data regarding which is the better treatment option.